1964
DOI: 10.1107/s0365110x64002547
|View full text |Cite
|
Sign up to set email alerts
|

The structures of Ba5Pb3, BaPb and BaPb3

Abstract: The structures of the compounds BasPb a, BaPb, and BaPb a have been determined. BasPb a has the body-centered tetragonal D8~ structure with a =9.038 +_0.010, c = 16.843-+0.017 A; the space group is I4/mcm and there are four formula units per unit cell. The room temperature modification of BaPb has the orthorhombic Bf structure with a =5.29 -+0.01, b= 12.60_+0.02, c =4.78 _+0-01 A; the space group is Cmcm and there are four formula units per unit cell. BaPb a is rhombohedral with a = 9-565 _+ 0.009 A, a = 44 ° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

1973
1973
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 3 publications
0
14
0
2
Order By: Relevance
“…x = 0.91–0.81: Die Reflexstatistiken der trigonal rhomboedrisch mit hoher Laue‐Klasse kristallisierenden Verbindungen zeigten keine zusätzlichen zonalen Auslöschungsbedingungen, so dass als mögliche Raumgruppen nur R $\bar{3}$ m und R 3 m verblieben. Die Verfeinerung der Struktur (Programm SHELXL‐97 [36,37] ) gelang in der zentrosymmetrischen Raumgruppe ausgehend von den (mit dem Programm STRUCTURE TIDY38 standardisierten) Parametern des TaCo 3 ‐Typs von BaPb 3 7. Bei Freigabe der Ba‐Besetzungsfaktoren zur statistischen Besetzung mit Strontium und Barium sowie anisotroper Behandlung der Auslenkungsparameter aller Atompositionen liessen sich die Intensitätsdaten bis zu R 1‐Werten von 0.064 bzw.…”
Section: Experimenteller Teilunclassified
See 1 more Smart Citation
“…x = 0.91–0.81: Die Reflexstatistiken der trigonal rhomboedrisch mit hoher Laue‐Klasse kristallisierenden Verbindungen zeigten keine zusätzlichen zonalen Auslöschungsbedingungen, so dass als mögliche Raumgruppen nur R $\bar{3}$ m und R 3 m verblieben. Die Verfeinerung der Struktur (Programm SHELXL‐97 [36,37] ) gelang in der zentrosymmetrischen Raumgruppe ausgehend von den (mit dem Programm STRUCTURE TIDY38 standardisierten) Parametern des TaCo 3 ‐Typs von BaPb 3 7. Bei Freigabe der Ba‐Besetzungsfaktoren zur statistischen Besetzung mit Strontium und Barium sowie anisotroper Behandlung der Auslenkungsparameter aller Atompositionen liessen sich die Intensitätsdaten bis zu R 1‐Werten von 0.064 bzw.…”
Section: Experimenteller Teilunclassified
“…Die gemischten ternären Erdalkalimetall‐Tristannide der Reihen CaSn 3 – SrSn 3 und SrSn 3 – BaSn 3 eignen sich noch besser als die entsprechenden, kürzlich im Detail untersuchten Plumbide3 zur systematischen Studie des Einflusses der Größe der A ‐Kationen auf die auftretende Stapelfolge, da hier mit CaSn 3 (Cu 3 Au‐Typ, ausschließlich c ‐Stapelung,4) und BaSn 3 (Ni 3 Sn‐Typ, ausschließlich h ‐Stapelung [5,6] ) beide Grenzfälle möglicher Stapelfolgen beobachtet werden; dagegen wird bei den Plumbiden für BaPb 3 nur die ( hhc ) 3 ‐Sequenz des TaCo 3 ‐Typs erreicht 7. Mit SrSn 3 (Mg 3 In‐Typ, hhcc ‐Stapelung8) ist ferner bereits eine gemischte Stapelfolge belegt.…”
Section: Introductionunclassified
“…Based on the observation that alloys richer in Y than the eutectic composition contain both ␣Al 3 Y and ␤Al 3 Y, Snyder [5] suggested that the transformation temperature is quite close to the eutectic temperature. The existence of two polymorphic forms of Al 3 Y has been confirmed by Snyder [5] and Bailey [15] for ␣Al 3 Y and by Snyder [5], Bruzzone and Ruggiero [16], van Vucht and Buschow [17], Sands et al [18], Dagerhamn and Westman [19] and Zeng and Wang [12] for ␤Al 3 Y.…”
Section: Introductionmentioning
confidence: 58%
“…The Ti atoms therefore will reduce the Pb atoms to some extent, so that one should consider Pb}Pb single bonds of negatively charged Pb atoms. Examples may be found among the Zintl phases, including 310 pm in Pb\ tetrahedra in KPb (26) and 313 pm in in"nite zigzag Pb\ chains in BaPb (27). These distances are considerably longer (by more than 7%) than the shortest Pb}Pb bond observed here (289.5 pm), which may be compared to the bond in the slightly de"cient linear Pb chain in Zr Pb \V (10).…”
Section: and Tamentioning
confidence: 74%